Association between Parkinson's disease and risk of prostate cancer in different populations: An updated meta-analysis. Issue 1 (December 2017) - Chen, Chunli; Zheng, Haiping; Hu, Zhiping
Abstract Recently, growing evidence has revealed a significant association between Parkinson's disease (PD) and cancer. However, controversy still exists concerning the association between PD and prostate cancer. A comprehensive article search for relevant published studies was performed using the online databases PubMed, Web of Science and Embase up to January 1, 2017. The pooled risk ratios (RRs) and their 95% confidence intervals (CIs) were calculated using the method of inverse variance with a random-effects model. Fifteen studies comprising 346, 153 PD patients were included in this study. The results of the present study showed that PD was significantly associated with a decreased risk of prostate cancer in the Western population (RR: 0.83, 95% CI: 0.72–0.95, P < 0.01), while an increased risk of prostate cancer was shown in the Asian population (RR: 1.80, 95% CI: 1.52–2.13, P < 0.001). In the subgroup analysis, the reduced risk of prostate cancer in PD patients from Western populations was consistent regardless of study design or study quality. In conclusion, PD was significantly associated with a reduced risk of prostate cancer in the Western population. The relationship between those conditions in the Asian population needs to be confirmed by future studies.